2021
DOI: 10.1186/s13073-021-00875-1
|View full text |Cite
|
Sign up to set email alerts
|

Persistent variations of blood DNA methylation associated with treatment exposures and risk for cardiometabolic outcomes in long-term survivors of childhood cancer in the St. Jude Lifetime Cohort

Abstract: Background It is well-established that cancer treatment substantially increases the risk of long-term adverse health outcomes among childhood cancer survivors. However, there is limited research on the underlying mechanisms. To elucidate the pathophysiology and a possible causal pathway from treatment exposures to cardiometabolic conditions, we conducted epigenome-wide association studies (EWAS) to identify the DNA methylation (DNAm) sites associated with cancer treatment exposures and examined… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 67 publications
2
45
0
Order By: Relevance
“…These have primarily concentrated on epigenetic ageing, and consistent with this study, have identified accelerated ageing in cancer survivors [ 43 46 ]. A recent study by Song et al [ 47 ] also performed an epigenome-wide association study (EWAS) to identify specific CpG sites exhibiting differential methylation in patients given specific therapies or combinations of therapies. They identified 935 CpG sites associated with individual treatments and 224 CpG sites associated with exposure to drug combinations.…”
Section: Discussionmentioning
confidence: 99%
“…These have primarily concentrated on epigenetic ageing, and consistent with this study, have identified accelerated ageing in cancer survivors [ 43 46 ]. A recent study by Song et al [ 47 ] also performed an epigenome-wide association study (EWAS) to identify specific CpG sites exhibiting differential methylation in patients given specific therapies or combinations of therapies. They identified 935 CpG sites associated with individual treatments and 224 CpG sites associated with exposure to drug combinations.…”
Section: Discussionmentioning
confidence: 99%
“…rs3093956 is a known hit for EAA-Hannum [ 15 ]; however, it has low LD ( r 2 =0.075) with rs28366133. Multiple striking DMRs were observed between survivors and controls in the HLA region, which might be due to the fact that genotoxic cancer treatments modified the epigenome among other physiological alterations in survivors and hence altered functional genomic links (e.g., eQTL, mQTL, and eQTM) [ 23 , 58 ], which may lead to either disruption or introduction of genetic associations with EAA. For the same reason, a substantial proportion (e.g., 20 out of 39 IEAA-associated SNPs) of previously reported genetic associations, including the most notable rs2736099 ( TERT ), were not replicated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The raw intensity was exported from Illumina Genome Studio and analyzed in R (version 3.6.3) using the minfi package [ 22 ]. Detailed quality controls (QCs) and data normalization were described previously [ 23 ]. After QCs, the data set comprised beta-values for 689,419 CpGs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMI represented body mass index. Principal components (PCs) decomposed from genomic methylation data have been used to control for potential confounding factors in genomic association analyses [ 42 ]. The change rate of eigenvalues suggested using the first five PCs, while PC 1 was highly collinear with buccal cell proportions (correlation r = 0.87) and PC 5 was associated with gender ( r = 0.45, p = 4.18 × 10 –11 ), race ( r = − 0.33, p = 3.17 × 10 –6 ), and PCSI at SA ( r = 0.19, p = 0.02).…”
Section: Methodsmentioning
confidence: 99%